Manajemen Keuangan: Analisis Likuiditas dan Solvabilitas dalam Meningkatkan Profitabilitas Perusahaan (Studi pada Industri Sub Sektor Makanan dan Minuman Tahun 2016–2020) - Ferisanti Ferisanti; Andri Andri; Syarqon Nazib; Leony Agustine (JURNAL ADMINISTRASI KANTOR, 2025)
The modern era today has created many obstacles that are quite heavy for business actors and are closely related to free trade to continue to innovate in the preparation of what methods will be carried out by the company in order to maintain its survival in the business world. Tight competition and also developments in the economic world in this era of globalization require that every management in a company always think creatively and progressively in order to be able to manage and adapt to changes that may occur in the company quickly and precisely. Therefore, it is very necessary to be implemented so that the company can continue to maintain the continuity of the company's existence in this modern era or the era of globalization. One industry that can survive well and even experience growth and development in modern times like this is the food and beverage industry. Keywords: Financial Management, Liquidity Analysis, Solvency Analysis, Company Profitability, Food and Beverage Industry.